Ghana's rice market - Ministry of Food and Agriculture, Ghana; International Food Policy Research Institute; Amewu, Sena; Arhin, Eunice; Danso, Jane; Doughan, Roland Ato; Nafrah, Christiana; Owusu, Ivy; Pauw, Karl (International Food Policy Research Institute, 2020)
Rice is an important staple in Ghana and is cultivated across all agroecological zones. Paddy rice output grew at around 10 percent per annum between 2008 and 2019, with an especially sharp increase of 25 percent in 2019. However, domestic production continues to fall short of demand with the import share of rice consumed remaining above 50 percent (MoFA 2018). This reflects a growing preference for rice among Ghanaian households, especially as consumers become wealthier and more urbanized. The large dependence on rice imports heightens concerns around foreign exchange imbalances and vulnerability to international rice price shocks. Hence, the National Rice Development Strategy of 2009 and the Planting for Food and Jobs (PFJ) campaign launched in 2017 not only prioritize rice but set ambitious expansion targets for domestic rice production (MOFA 2017a). Policy objectives include substituting rice imports and producing a higher-quality product that is more acceptable to Ghanaian consumers and can compete with imported rice.